Layanan pelanggan berbasis Natural Language Processing melalui chatbot pada aplikasi pesan - Ardiansyah, Ricky Herman; Sulaksono, Aditya Galih (Universitas Merdeka Malang, 2023)
The form of service to customers in an appropriate, fast and easy way is the main thing that every business actor needs to pay attention to. Including how to communicate with customers virtually through messaging applications. With the sophistication of information technology, it can be used to create new opportunities for business actors. One of them is Natural Language Processing or NLP technology which allows machine interaction with human natural language. This study aims to provide messaging services to customers effectively and efficiently. Implementation is done by using a chatbot on the messaging application. Chatbot is designed to be able to respond to customer messages automatically and in real-time by implementing the NLP method. Based on the observations made, it is known that the three categories of questions most frequently asked by customers are location, price list, and pick-up service. The results of the study show that chatbots created using natural language can be easily understood and used by customers. Business actors are also facilitated because they no longer need to reply to customer messages one by one, so that service to customers becomes more responsive and optimal.